A Novel Fast-Setting Strontium-Containing Hydroxyapatite Bone Cement With a Simple Binary Powder System - Sun, Lijuan; Li, Tongyang; Yu, Sen; Mao, Mengmeng; Guo, Dagang (Frontiers in Bioengineering and Biotechnology, 2021)
In recent years, strontium-substituted calcium phosphate bone cement (Sr-CPC) has attracted more and more attentions in the field of bone tissue repair due to its comprehensive advantages of both traditional CPC and Sr ions. In this study, an important Sr-containing salt α-Ca3-xSrx(PO4)2 had been synthesized with a simpler one-step method and relatively lower synthesis temperature and a novel Sr-CPC had been developed based on a simple binary Sr-containing cement powder of α-Ca3-xSrx(PO4)2/Ca4(PO4)2O. The physicochemical properties and hydration mechanism of this Sr-CPC at various Sr contents were intensively investigated. The setting product of this Sr-CPC after set for 72h is a single-phase Sr-containing hydroxyapatite, and its compressive strength slightly decreased and its setting time extended with the increase of Sr content. The hydration process concluded the initial formation of the medium product CaHPO4∙2H2O (30min~1h), the following complete hydration of Ca4(PO4)2O and the initially-formed CaHPO4∙2H2O (2~6h) and the final self-setting of α-Ca3-xSrx(PO4)2 (6h~). The compressive strength of Sr-CPC, which was closely related to the transformation rate of Sr-containing hydroxyapatite, tended to increase with the extension of hydration time. In addition, Sr-CPC possessed favorable cytocompatibility and the effect of Sr ions on cytocompatibility of Sr-CPC was not obvious at low Sr contents. The present study suggests α-Ca3-xSrx(PO4)2 is a kind of vital Sr-containing salt source which is useful to develop some novel Sr-containing biomaterials. Also, the new Sr-containing cement system based on this simple binary α-Ca3-xSrx(PO4)2/Ca4(PO4)2O cement powder displayed an attractive clinical application potential in orthopedics.